Light-mediated self-organization of sunflower stands increases oil yield in the field - López Pereira, Mónica (2017)
Here, we show a unique crop response to intraspecific interference, whereby neighboring sunflower plants in a row avoid each other by growing toward a more favorable light environment and collectively increase production per unit land area. In high-density stands, a given plant inclined toward one side of the interrow space, and the immediate neighbors inclined in the opposite direction. This process started early as an incipient inclination of pioneer plants, and the arrangement propagated gradually as a “wave” of alternate inclination that persisted until maturity. Measurements and experimental manipulation of light spectral composition indicate that these responses are mediated by changes in the red/far-red ratio of the light, which is perceived by phytochrome. Cellular automata simulations reproduced the patterns of stem inclination in field experiments, supporting the proposition of self-organization of stand structure. Under high crop population densities (10 and 14 plants per m2), as yet unachievable in commercial farms with current hybrids due to lodging and diseases, self-organized crops yielded between 19 and 47% more oil than crops forced to remain erect.